Sistem Kepercayaan Tokopedia dalam Meningkatkan Pembelian Pelanggan - Firmanysah, Wahyu; Ghibran, Maulana; A'isyah, Siti; Anisyah, Siti; Rengganih, Riri; Rahmawati, Titi (Universitas Multi Data Palembang, 2024)
This study aims to analyze customer confidence in purchasing decisions with purchase interest as an intervening variable in Tokopedia E-Commerce. This type of research is qualitative using the literature study method. The result of this study is that customer trust has a positive effect on purchasing decisions with purchase interest as an intervening variable in tokopedia E-Commerce and efforts made by tokopedia to increase customer trust.